Verrucous hemangioma and angiokeratoma circumscriptum neviforme. Variants of the same disease or separate entities? - Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
Verrucous hemangioma (VH) and angiokeratoma circumscriptum neviforme (ACN) have identical natural history and can hardly be differentiated on clinical grounds. The histological examination and imaging techniques show in ACN exclusive involvement of the papillary dermis while in VH the subcutaneous fat is also affected. Some histological and immunohistochemical findings seem to differentiate ACN, which acts like a malformation, from VH presenting some aspects of a proliferative tumor alongside with other aspects of malformation, probably indicating that the separation of vascular lesions in malformation and tumor is less clear than you think. Regardless of nosologic classification it is clinically important to exclude or highlight the involvement of the subcutaneous tissue, which has important implications from the therapeutic point of view.